2003
DOI: 10.4049/jimmunol.170.3.1136
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Profile of Chemokine Receptor Expression on Human Plasma Cells Accounts for Their Efficient Recruitment to Target Tissues

Abstract: We systematically examined the repertoire of chemokine receptors expressed by human plasma cells. Fresh bone marrow plasma cells and myeloma cells consistently expressed CXCR4, CXCR6, CCR10, and CCR3. Accordingly, plasma cells responded to their respective ligands in chemotaxis and very late Ag-4-dependent cell adhesion to fibronectin. Immobilized CXC chemokine ligand (CXCL)16, a novel transmembrane-type chemokine and CXCR6 ligand, also directly induced adhesion of plasma cells without requiring Gαi signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
205
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 229 publications
(211 citation statements)
references
References 18 publications
4
205
2
Order By: Relevance
“…The axis of CXCR4/CXCL12 plays an important role in metastasis of many tumors (9)(10)(11)(12)(13)(14)(22)(23)(24)(25). Abnormal expression of CXCR4 or CXCL12 has been observed in solid tumors such as ovarian cancer (30), rhabdomysarcoma (26), nasopharyngeal carcinoma (21), melanoma (27), colorectal cancer (28), pancreatic cancer (24), and breast cancer (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The axis of CXCR4/CXCL12 plays an important role in metastasis of many tumors (9)(10)(11)(12)(13)(14)(22)(23)(24)(25). Abnormal expression of CXCR4 or CXCL12 has been observed in solid tumors such as ovarian cancer (30), rhabdomysarcoma (26), nasopharyngeal carcinoma (21), melanoma (27), colorectal cancer (28), pancreatic cancer (24), and breast cancer (7).…”
Section: Discussionmentioning
confidence: 99%
“…CXCL12 (stromal cell-derived factor-1, SDF-1) is a member of the CXC chemokine subfamily and binds to CXC chemokine receptor 4 (CXCR4). The expressions of CXCL12 and CXCR4 have been detected in several cancer cells indicating that they may be important in metastasis of tumor cells (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Because EBV-immortalized B cells resemble plasma cells in terms of the continuous production of Igs (24), we hypothesized that CCR10 might be selectively expressed at the terminal differentiation stage of B cells. We have indeed demonstrated that a substantial fraction of plasma cells derived from human bone marrow expresses CCR10 and efficiently migrates to its ligands CCL27 and CCL28 (25). Furthermore, Butcher and his colleagues (26,27) have demonstrated that IgA-ASCs present in various mucosal tissues commonly express CCR10.…”
Section: 25-dihydroxyvitamin D 3 Induces Ccr10 Expression In Terminmentioning
confidence: 91%
“…CXCR6, the only known receptor for CXCL16, is also known as Bonzo, TYMSTR, and STRL33, and is a newly characterized chemokine receptor initially described as an HIV coreceptor expressed by a subset of memory/T effector cells, natural killer cells, and plasma cells (26)(27)(28)(29)(30). The present study directly addresses the participation of both CXCR6 and its ligand CXCL16 in leukocyte migration in RA.…”
mentioning
confidence: 85%
“…These chemokines contain a small cytoplasmic domain with a "YXPV" motif that is a potential tyrosine phosphorylation and SH2-binding site, and is preferentially expressed by type 1 lymphocytes. Finally, CXCL16 has a unique receptor-ligand interaction, much like fractalkine (24)(25)(26). These characteristics are important, considering the proinflammatory functions of fractalkine in RA and in rat adjuvant-induced arthritis (AIA) (3,4).…”
mentioning
confidence: 99%